Traditions of the Saratov Region in Ethnocultural Practices - Irina Y. Zamchalova (Publishing house "Sreda", 2020)
The article deals with the preservation of the cultural traditions of some peoples living in the territory of the Saratov Region. The aim of the study is to show that the preservation of traditions is a source of further development and the existence of ethnic groups. Methods. During the study the following methods are used: typological, system analysis, functional approach. There is a search for new forms of recreation of national traditions, and they are very productive. The characteristic of the historical reconstructions, national festivals successfully held in the Saratov Region is described. Results. It was found that such forms demonstrate effective partnership between representatives of different generations. They contribute to the popularization of cultural and historical heritage, spiritual and moral education. The author outlines that youth, children, elderly people demonstrate their creative achievements. It is emphasized that festivals perform cultural and educational functions, involve in the process of a detailed study of history, rites, art of the ethnic groups represented. Creative groups, historical reenactors, and participants in school ethnographic circles are active in creating an atmosphere of a traditional way of life. A heuristic principle is developing among the participants of events. When they are organized, social partnerships between administrative structures, universities, and private business representatives are demonstrated. Conclusions. Based on the analysis of the results of ethnocultural events, we believe that it is necessary to improve such forms that help to develop traditions in the culture of ethnic groups. There is a growing interest in the topic of restoring the traditional ways of life of the Volga peoples. There is promise in the development of this direction and the need for further theoretical justification of the significance of ethnocultural practices.